Mechanistic Probes for the Epimerization Domain of Nonribosomal Peptide Synthetases. (9th November 2018) - Kim, Woojoo E.; Patel, Ashay; Hur, Gene H.; Tufar, Peter; Wuo, Michael G.; McCammon, J. Andrew; Burkart, Michael D.
Abstract: Nonribosomal peptide synthetases (NRPSs) are responsible for the synthesis of a variety of bioactive natural products with clinical and economic significance. Interestingly, these large multimodular enzyme machineries incorporate nonproteinogenicd ‐amino acids through the use of auxiliary epimerization domains, convertingl ‐amino acids intod ‐amino acids that impart into the resulting natural products unique bioactivity and resistance to proteases. Due to the large and complex nature of NRPSs, several questions remain unanswered about the mechanism of the catalytic domain reactions. We have investigated the use of mechanism‐based crosslinkers to probe the mechanism of an epimerization domain in gramicidin S biosynthesis. In addition, MD simulations were performed, showcasing the possible roles of catalytic residues within the epimerization domain. Abstract : Letting the catalytic residues out of the bag : Many nonribosomal peptide synthetases (NRPSs) incorporate nonproteinogenicd ‐amino acids through the use of epimerization (E) domains. We have investigated the use of mechanism‐based crosslinkers to probe the E domain in gramicidin S biosynthesis and used MD simulations to evaluate the roles of catalytic residues.